High throughput mechanochemistry: application to parallel synthesis of benzoxazines. Issue 5 (2nd January 2018) - Martina, K.; Rotolo, L.; Porcheddu, A.; Delogu, F.; Bysouth, S. R.; Cravotto, G.; Colacino, E.
Abstract : Mechanochemical "parallel synthesis": processing 12 samples simultaneously allowed fast screening of the optimum reaction conditions and high throughput preparation of benzozaxine derivatives, including a fungicide. Abstract : We describe herein an unprecedented mechanochemical " parallel synthesis " of 3, 4-dihydro-2 H -benzo[ e ][1, 3]oxazine derivatives via a one pot three component reaction. The new milling system uses a multiposition jar (variable sizes are possible), allowing for the processing of up to 12 samples simultaneously, leading to the formation of a fungicide and a building block for polymer preparation with higher throughput compared to standard milling devices.